THE RIGHT TO A FAIR TRIAL IN THE DYNAMIC INTERPRETATION OF THE EUROPEAN COURT OF HUMAN RIGHTS - Alexandra PANAIT (Challenges of the Knowledge Society)
The European Court of Human Rights has constantly highlighted the importance of Article 6 of the Convention and by a dynamic interpretation, the jurisprudence of the Strasbourg Court has gradually enriched the content and the practical impact of the treaty text, recognizing various additional guarantees compared to those expressly provided for by the Convention, such as certain specific applications of the equity principle and the national court’s obligations of loyalty and compliance with the Convention, which represent essential elements of the general concept of a fair trial.